The School and Its Problems through Pupils’ Eyes - Lamanauskas, Vincentas (Acta Paedagogica Vilnensia, 1997)
This is a presentation of the results of a sociological survey that took place in Lithuanian schools in 1990-1991 and 1991-1992. We look at the school through pupils’ eyes, because the information received in such way is very important. We are sure that time is changing the opinions and problems, and the results in 1993-1994 may be quite different. The article deals with these main problems: 1) the constructive interactions between pupils and teachers aren’t suitable; 2) the school’s structure, content of education and the organization of the teaching process are often inadequate for the constantly rising social requirements; 3) the school’s material base is weak; 4) there is an apathetic, public indifference to the school, reforms, and the teacher.